Demonstration of acid and water recovery systems: Applicability and operational challenges in Indian metal finishing SMEs. (1st July 2018) - Balakrishnan, M.; Batra, R.; Batra, V.S.; Chandramouli, G.; Choudhury, D.; Hälbig, T.; Ivashechkin, P.; Jain, J.; Mandava, K.; Mense, N.; Nehra, V.; Rögener, F.; et al.
Abstract: Diffusion dialysis, acid retardation and nanofiltration plants were acquired from Europe and demonstrated in several Indian metal finishing companies over a three year period. These companies are primarily small and medium enterprises (SMEs). Free acid recovery rate from spent pickling baths using diffusion dialysis and retardation was in the range of 78–86% and 30–70% respectively. With nanofiltration, 80% recovery rate of rinse water was obtained. The demonstrations created awareness among the metal finishing companies to reuse resources (acid/water) from the effluent streams. However, lack of efficient oil separators, reliable chemical analysis and trained personnel as well as high investment cost limit the application of these technologies. Local manufacturing, plant customization and centralized treatment are likely to encourage the uptake of such technologies in the Indian metal finishing sector. Graphical abstract: Image 1 Highlights: Diffusion dialysis, acid retardation and nanofiltration demonstrated in Indian SMEs. Spent acid recovery was 78–86% (diffusion dialysis) and 30–70% (retardation). Rinse water recovery was 80% with nanofiltration. Demonstrations created awareness on resources recovery and pollution reduction. Local manufacturing and plant customization essential for technology adoption.